The Impact of Macromedia Flash Utilization in Cone Material on Class IX Students' Conceptual Comprehension - Aswita, Nova; Widiawati, Widiawati; Widyaningrum, Indah (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
This research seeks to ascertain the impact of Macromedia Flash on the conceptual comprehension of ninth-grade students at SMP Negeri 5 Pagaralam regarding cone content. This research employs an experimental design utilizing a Pre-test - Post-test control group methodology. The research utilized observation sheets and essay-format test question sheets as instruments. This study included 29 students who engaged with Macromedia Flash media and 30 students who received conventional instruction. Data gathering methods are conducted by observation and testing. The research findings demonstrate that students utilizing Macromedia Flash learning media exhibit a superior comprehension of topics compared to those engaged in traditional learning methods. The average percentage score for concept understanding indicators was 83.28 in the experimental class and 67.07 in the control class. The experimental class surpasses the control class. Consequently, the utilization of Macromedia Flash affects pupils' comprehension of topics.